Continuously Conducted Selective Hydrogenation of Benzene to Cyclohexene in a Four‐Phase System1. Issue 8 (25th June 2015) - Spod, Hendrik; Lucas, Martin; Claus, Peter
Abstract Currently, the production of nylon 6 and nylon 6.6 is based on the complete hydrogenation of benzene to cyclohexane over nickel or platinum catalysts and its subsequent oxidation at very low conversions to a mixture of cyclohexanol/cyclohexanone. This mixture is further reacted to ϵ‐caprolactam or adipic acid. Alternatively, the reaction can be carried out by selective hydrogenation of benzene to cyclohexene and subsequent hydration with acidic catalysts to cyclohexanol. A laboratory method for the selective hydrogenation of benzene in a continuous stirred‐tank reactor (CSTR) using a gas/liquid/liquid/solid system is presented.